2017
DOI: 10.1590/1678-98652017000400002
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and metabolic profile in adults with vitamin D deficiency

Abstract: A B S T R A C T ObjectiveTo investigate the body composition and metabolic profile in individuals in terms of different concentrations of serum vitamin D, ranging from deficiency to sufficiency. MethodsA cross-sectional study of 106 adults of both genders, who were divided into three groups according to vitamin D levels: deficiency: <20ng/mL; insufficiency: 20-29.9ng/mL; and sufficiency: 30-100ng/mL. Anthropometric evaluation included weight, height, and body circumferences. Fat mass and lean mass were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 50 publications
1
13
0
1
Order By: Relevance
“…In the specific case of Brazil, although it is a tropical country with a year-round incidence of solar radiation, a significant prevalence of 25(OH)D deficiency has also observed [14,15]. Recent evidence confirms similar findings in other populations around the world [16,17] that rekindles the question of which factors could be associated with a lower serum 25(OH)D levels in the adult population.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In the specific case of Brazil, although it is a tropical country with a year-round incidence of solar radiation, a significant prevalence of 25(OH)D deficiency has also observed [14,15]. Recent evidence confirms similar findings in other populations around the world [16,17] that rekindles the question of which factors could be associated with a lower serum 25(OH)D levels in the adult population.…”
Section: Introductionmentioning
confidence: 59%
“…Blood samples were collected using a vacuum-assisted blood collection system and disposable material after 12 hours of fasting. The status of 25(OH)D was determined according to the following reference values: sufficient (≥30.0ng/ml), insufficient (21.0ng/ml to 29.9ng/ml) and deficient (≤20.9ng/ml) [14,26]. The season of the year when blood collection was performed was also evaluated and categorized as: winter, autumn, spring and summer.…”
Section: E T H O D Smentioning
confidence: 99%
“…Analysis by Rocha LM et al . [14] in a cross-sectional study of 106 adults of both genders vitamin D deficiency had higher triglycerides, VLDL, fasting blood glucose, insulin, glycated hemoglobin, BMI, waist circumference, and HOMA-IR than those of the vitamin D sufficient group ( P < 0.05)…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a growing need for studies that include as many risk factors as possible. [16][17] Researchers from China conducted a comprehensive review of the literature and a meta-analysis to assess the association between serum levels and dietary intake of vitamin D with the risk of lung cancer. As a result, they found that those with higher serum vitamin D levels had a 16% lower risk of developing lung cancer.…”
Section: Methods Introductionmentioning
confidence: 99%